Eosinophilic Laryngitis in Children with Aerodigestive Dysfunction. (27th March 2015) - Yawn, Robert J.; Acra, Sari; Goudy, Steven L.; Flores, Raina; Wootten, Christopher T.
Abstract : Objective: To describe the presence of laryngeal eosinophils and associated symptomatology in patients with aerodigestive dysfunction. Study Design: Case series with chart review. Setting: Single tertiary pediatric referral center. Subjects: Eighty‐one consecutive pediatric patients referred to a multidisciplinary aerodigestive clinic with upper airway concerns. Methods: Microlaryngoscopy and posterior arytenoid biopsy, flexible bronchoscopy, esophagogastroduodenoscopy and esophageal biopsy, and impedance probe testing were performed as indicated by clinical symptoms. Positive versus negative posterior arytenoid biopsy for eosinophils and the presence or absence of concomitant histopathological laryngitis and/or esophagitis were measured. Results: Nine of 81 (11%) patients had positive laryngeal biopsy for eosinophils (range, 1‐29 eosinophils/high‐powered field [HPF]). Three of these 9 patients also had concurrent biopsy‐proven eosinophilic esophagitis, while 8 of 81 total patients had biopsy‐proven eosinophilic esophagitis. The frequency of biopsy‐proven eosinophilic esophagitis was higher in patients with posterior arytenoid eosinophils versus patients without laryngeal eosinophils (33% versus 6.9%, P =. 0408). Conclusions: Eosinophilic inflammation in the larynx has not been described in children with complex aerodigestive complaints. Posterior arytenoid eosinophils may serve as a marker of chronic laryngeal inflammation in children with aerodigestive dysfunction, although their exact role in this inflammation remains unclear. In our population, >15 eosinophils/HPF within posterior arytenoid biopsies was associated with concomitant eosinophilic esophagitis.